IMPLEMENTATION OF WEST PAPUA REGIONAL REGULATION NO. 5 YEAR 2023 AND GOVERNOR'S REGULATION NO. 16 YEAR 2024: LITERATURE STUDY ON THE DYNAMICS OF PEOPLE'S MINING LAW: IMPLEMENTASI PERATURAN DAERAH PAPUA BARAT NO. 5 TAHUN 2023 DAN PERATURAN GUBERNUR NO. 16 TAHUN 2024: STUDI KEPUSTAKAAN TENTANG DINAMIKA HUKUM PERTAMBANGAN RAKYAT - Karubaba, Andrew; Hutapea, Ricardo O.M.; Kabes, Rico H. (Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2025)
This study examines the legal substance and regulatory system in West Papua Regional Regulation Number 5 of 2023 concerning Community Mining and West Papua Governor Regulation Number 16 of 2024 concerning Mineral and Coal Mining Management. The normative legal method uses literature studies to analyze the direction of the West Papua Provincial Government's policy in managing community mining under the Special Autonomy framework. The study results indicate inconsistencies between regional policies and national forestry regulations, especially regarding determining Community Mining Areas (WPR), most located in protected forest areas. In addition, there are no explicit provisions regarding the involvement of indigenous peoples as the main stakeholders in the licensing process. For this reason, it is necessary to take strategic steps to align policies between the central and regional governments with local conditions and to formally recognize the rights and roles of Indigenous peoples in governing community mining in West Papua.